The uremic toxin adsorbent AST-120 abrogates cardiorenal injury following myocardial infarction - Lekawanvijit S. (2014)
An accelerated progressive decline in renal function is a frequent accompaniment of myocardial infarction (MI). Indoxyl sulfate (IS), a uremic toxin that accumulates from the early stages of chronic kidney disease (CKD), is contributory to both renal and cardiac fibrosis. IS levels can be reduced by administration of the oral adsorbent AST-120, which has been shown to ameliorate pathological renal and cardiac fibrosis in moderate to severe CKD. However, the cardiorenal effect of AST-120 on less severe renal dysfunction in the post-MI setting has not previously been well studied. MI-induced Sprague-Dawley rats were randomized to receive either AST-120 (MI+AST-120) or were untreated (MI+Vehicle) for 16 weeks. Serum IS levels were measured at baseline, 8 and 16 weeks. Echocardiography and glomerular filtration rate (GFR) were assessed prior to sacrifice. Renal and cardiac tissues were assessed for pathological changes using histological and immunohistochemical methods, Western blot analysis and real-time PCR. Compared with sham, MI+Vehicle animals had a significant reduction in left ventricular ejection fraction (by 42%, p<0.001) and fractional shortening (by 52%, p<0.001) as well as lower GFR (p<0.05) and increased serum IS levels (p<0.05). A significant increase in interstitial fibrosis in the renal cortex was demonstrated in MI+Vehicle animals (p<0.001). Compared with MI+Vehicle, MI+AST-120 animals had increased GFR (by 13.35%, p<0.05) and reduced serum IS (p<0.001), renal interstitial fibrosis (p<0.05), and renal KIM-1, collagen-IV and TIMP-1 expression (p<0.05). Cardiac function did not change with AST-120 treatment, however gene expression of TGF-β1 and TNF-α as well as collagen-I and TIMP-1 protein expression was decreased in the non-infarcted myocardium (p<0.05). In conclusion, reduction of IS attenuates cardio-renal fibrotic processes in the post-MI kidney. KIM-1 appears to be a sensitive renal injury biomarker in this setting and is correlated with serum IS levels. © 2013 Lekawanvijit et al.